Mixed‐integer nonlinear programming framework for combined heat and power units with nonconvex feasible operating region: Feasibility, optimality, and flexibility evaluation - Razavi, Seyed‐Ehsan; Javadi, Mohammad Sadegh; Esmaeel Nezhad, Ali (International transactions on electrical energy systems, 2019)
This paper presents an optimization framework to determine the optimal operating points of combined heat and power (CHP) units with nonlinear, nonconvex feasible operating region (FOR). The mentioned problem is the economic dispatch (ED) of heat‐only units, thermal units, and CHP units. Also, the electric units are of thermal technology while their valve‐point impact is taken into consideration. Also, the heat power curve of heat‐only units is nonlinear. It is noted that the FOR of CHP units has been defined both as convex and nonconvex regions. For those with nonconvex characteristic, a method is proposed to convert it into a convex characteristic. Accordingly, a separate binary variable must be defined to determine the optimal operating point in each convex region. Thus, the presented problem in this paper is of mixed‐integer nonlinear programming (MINLP) type modeled in General Algebraic Modeling System (GAMS) software. In this respect, different case studies have been presented to assess the optimality, feasibility, and the flexibility of the model. It is noteworthy that the valve‐point effect of thermal units and different FORs of CHP units as well as the electrical power losses have been considered.